Automation Reverse Osmosis System using Computer Analyze - Tipsuwanpom, V.; Anotaiadikoon, J.; Gulpanich, S.; Krongratana, V.; Witheephanich, K. (My University, 2003)
As Pure & Drinking water system is universally employed in Industrial,Reverse Osmosis System (ROS) has been becoming increasingly popular due to efficiency in Salt & Organic Rejection of it. However membrane system need regular cleaning. This paper present a new method for automation cleaning Reverse Osmosis System using Computer monitoring Process & analyze Trend of membrane performance & discuss enter to automation cleaning. The membrane performance consist of TDS, Water Flow, Pressure and Temperature. These variable analyzed for automation cleaning in order to maintain productivity and performance of RO System.
Keywords: Concentrate; Membrane; Permeate; PLC; ROS; TDS